Impact of Family Involvement and Longevity Goals on Small Family Firm Performance in Southern Punjab, Pakistan - Ullah, Sami; Iqbal, Tehrim; Yaseen, Muhammad Noaman; Mohsin, Zeeshan; Bakhsh, Khuda (Pakistan Journal of Humanities and Social Sciences, 2024)
This study is designed to find out the effect of family long-term goals on family firms’ performance in the underdeveloped region of Pakistan. The study addressed two research questions: how does family participation in management affect the performance of family firms? Does there exist moderation between family long-term goals and family participation in management and the effect on the performance of the family firms? Data was collected from 137 very small and small family firms of the southern Punjab (Pakistan). We used partial least square regression to determine the moderating role of family longevity goal in firm performance. Results showed that there was no significant direct impact of family participation in management on firm performance. However, the effect of family longevity goals was significant and positive (0.20) on family firm’s performance. Relationship between performance of family firms and family participation in management (0.17) depends on family longevity goals implying that family firms can contribute better in business performance.